2013
DOI: 10.1364/ol.38.003298
|View full text |Cite
|
Sign up to set email alerts
|

Robust moisture and thermally stable phosphor glass plate for highly unstable sulfide phosphors in high-power white light-emitting diodes

Abstract: Potential white light-emitting diode (LED) phosphor SrGa2S4, which remains superfluous due to its unstable nature in the presence of moisture, was successfully integrated in a high-power white LED system by developing a glass-based phosphor plate. A glass system with softening temperature at around 600°C, which lies far below the possible decomposition temperature of the sulfide phosphor, provides a stable shield. Physical properties such as thermal stability, transparency, and lower porosity along with chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…Lee et al [12] designed segmented PiGs with CASN:Eu 2 , but they can only be applied to large multi-chip LEDs since they need to be diced and reassembled. The intermixing of SrGa 2 S 4 :Eu 2 for green and CASN:Eu 2 was also reported [13] using SiO 2 -ZnO-B 2 O 3 glass, which can be sintered above 600°C. However, the CASN:Eu 2 phosphor starts to degrade at 600°C.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Lee et al [12] designed segmented PiGs with CASN:Eu 2 , but they can only be applied to large multi-chip LEDs since they need to be diced and reassembled. The intermixing of SrGa 2 S 4 :Eu 2 for green and CASN:Eu 2 was also reported [13] using SiO 2 -ZnO-B 2 O 3 glass, which can be sintered above 600°C. However, the CASN:Eu 2 phosphor starts to degrade at 600°C.…”
mentioning
confidence: 61%
“…As shown in the figure, the CASN:Eu 2 starts to lose its color and PL intensity from 600°C and drops thereafter. The oxidation of Eu 2 into Eu 3 and possible chemical decomposition of nitride phosphors at the sintering temperature are believed to be responsible for the thermal degradation [13,14]. This makes it hard to adjust the chromaticity of the PiGs with conventional glasses at sintering temperatures higher than 600°C.…”
mentioning
confidence: 99%
“…In addition, the fabrication of bulk luminescent material of millimeter thickness became not practically needed for a WLED. Therefore, the fabrication of inorganic luminescence layers by a single and cost‐efficient process supported by robust moisture and thermal stability is highly desirable in high‐power white light‐emitting diodes …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not only YAG:Ce 3+ -based PiG but also PiG with phosphors of various emission wavelengths have been reported by many researchers. Lee et al 65 reported the feasibility of using PiG as an encapsulant for highly unstable SrGa 2 S 4 :Eu 2+ sulfide phosphors, which were not previously used in wLED applications because of high chemical instability. Zhu et al 66 developed a green PiG using β-SiAlON:Eu 2+ phosphor under various blue laser flux densities.…”
Section: Glass Phosphor Plate (Gpp)mentioning
confidence: 99%